2018
DOI: 10.21580/pjpp.v3i1.2052
|View full text |Cite
|
Sign up to set email alerts
|

Aplikasi Rasch Model dalam Mengevaluasi Intelligenz Structure Test (IST)

Abstract: <p class="IABSTRAK"><strong>Abstract:</strong> The concept of objective measurement in the social sciences and educational assessment must have five criteria: 1) Gives a linear measure with the same interval; 2) Conduct a proper estimation process; 3) Finding unfeasible items (misfits) or outliers; 4) Overcoming the lost data; 5) Generate replicable measurements (independent of the parameters studied). These five conditions of measurement, so far only Rasch model that can fulfill it. The qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 1 publication
1
3
0
6
Order By: Relevance
“…The overall quality of the SE-revised items is quite good because there are no misfit items observed. This finding is in line with previous studies which found several items in the original SE that were not functioning properly and needed improvement (Elvira, 2011;Rahmawati, 2014;Suryani, 2018). After the revision was carried out, all items of the SE was deemed fit, meaning that there was an increase in the quality of items after being revised.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The overall quality of the SE-revised items is quite good because there are no misfit items observed. This finding is in line with previous studies which found several items in the original SE that were not functioning properly and needed improvement (Elvira, 2011;Rahmawati, 2014;Suryani, 2018). After the revision was carried out, all items of the SE was deemed fit, meaning that there was an increase in the quality of items after being revised.…”
Section: Discussionsupporting
confidence: 90%
“…Data analysis was carried out using computerized rasch model through the Winstep 3.73 for Windows application program, which produces results that has been sorted based on difficulty level -from the highest difficulty level to the lowest difficulty level, making it easier to identify which questions are difficult and which questions are easy (Suryani, 2018). The data analysis includes analysis of unidimensionality, reliability, fit items, item difficulty index, and DIF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an open access article under CC-BY-SA license (https://creativecommons.org/licenses/by-sa/4.0/) lebih komprehensif dan konkrit dalam pengukuran instrumen tes, hal ini karena model Rasch melibatkan dua aspek parameter yaitu (a) abilitas siswa, dan (b) tingkat kesulitan soal (Mariam et al, 2018;Suryani, 2018).…”
Section: Juga Menegaskan Bahwa Model Rasch Memberikan Deskripsi Yangunclassified
“…Menurut Suryani (2018) konsep pengukuran objektif dalam ilmu sosial dan penilaian pendidikan harus memiliki lima kriteria: 1) Memberikan ukuran yang linier dengan interval yang sama; 2) Melakukan proses estimasi yang tepat; 3) Menemukan item yang tidak tepat (misfits) atau tidak umum (outlier); 4) Mengatasi data yang hilang; 5) Hasilkan pengukuran yang replicable (independen dari parameter yang diteliti). Kelima kondisi pengukuran ini, sejauh ini hanya Rasch Model yang bisa memenuhinya.…”
unclassified